Headspace delivery of limonene from the serum and non-serum fractions of orange juice in-vitro and in-vivo - Fernandez-Vazquez, Rocio; Linforth, Rob S.T.; Hort, Joanne; Hewson, Emma Louise; Hernanz Vila, Dolores; Heredia Mira, F.J,; Vicario, Isabel; Fisk, Ian D. (Elsevier, 2013)
The impact of orange juice pulp on the physical release of limonene to the headspace of freshly prepared orange juice was evaluated both in-vitro and in-vivo. Atmospheric pressure chemical ionization mass spectrometry was used to analyse the impact of the matrix on the dynamic release of the volatile aroma compound, limonene, in orange juice. Pulp and aqueous serum was isolated (by centrifugation and filtration) from freshly prepared orange juice and subsequently reconstituted at varying pulp addition levels in serum (0g/100 g–20 g/100 g, wwb). The addition of pulp significantly enhanced the static headspace concentration of limonene with a 210 fold increase with 10 g/100 g pulp addition. In addition, pulp enhanced the ability of the orange juice serum to replenish limonene in the headspace after dynamic headspace dilution. The release of limonene was studied under realistic consumer consumption conditions (In-nose delivery) by atmospheric pressure chemical ionisation-mass spectrometry; pulp significantly enhanced the amount of limonene exhaled in the nasal airflow (retronasal delivery). Surprisingly, given the variations in limonene concentration, naïve consumers did not perceive samples as significantly different on consumption. This is presumably due to the wide range of other aroma compounds not evaluated in this study that contribute to the perceived aroma.